Development of adjuvant nanocarrier systems for seasonal influenza A (H3N2) vaccine based on Astragaloside VII and gum tragacanth (APS). Issue 28 (19th June 2019) - Yakuboğulları, Nilgün; Genç, Rükan; Çöven, Fethiye; Nalbantsoy, Ayşe; Bedir, Erdal
Highlights: AST-VII and Gum Tragacanth was used to prepare an adjuvant nanocarrier system. Efficiency of the carrier system was tested with inactivated H3N2 vaccine. Th1/Th2 mixed and Th17 immune responses were stimulated in vivo. The inductions of IFN-γ, IL-17A, IgG1, IgG2a were significant. The nanocarrier system remarkably increased splenocyte proliferation. Abstract: Adjuvants are chemical/biological substances that are used in vaccines to increase the immunogenicity of antigens. A few adjuvants have been developed for use in human vaccines because of their limitations including lack of efficacy, unacceptable local or systemic toxicity, the difficulty of manufacturing, poor stability, and high cost. For that reasons, novel adjuvants/adjuvant systems are under search. Astragaloside VII (AST-VII), isolated from Astragalus trojanus, exhibited significant cellular and humoral immune responses. The polysaccharides (APS) obtained from the roots of Astragalus species have been used in traditional Chinese medicine and possess strong immunomodulatory properties. In the present study, the immunomodulatory effects of a newly developed nanocarrier system (APNS: APS containing carrier) and its AST-VII containing formulation (ANS: AST-VII + APNS), on seasonal influenza A (H3N2) vaccine were investigated. Inactivated H3N2 alone or its combinations with test compounds/formulations were intramuscularly injected into Swiss albino mice. Four weeks after immunization, the immune responses were evaluated in terms of antibody and cytokine responses as well as splenocyte proliferation. APNS demonstrated Th2 mediated response by increasing IgG1 antibody titers, whereas ANS showed response towards Th1/Th2 balance and Th17 by producing of IFN-γ, IL-17A and IgG2a. Based on these results, we propose that APNS and ANS are good candidates to be utilized in seasonal influenza A vaccines as adjuvants/carrier systems.